Estudo de compostos de coordenação de cobalto e labilidade eletrônica - Marcos Antonio Ribeiro (2013)
The search for new functional materials involves the development of bistable molecules exhibiting different electronic states with distinct properties at the ambient condition (temperature, pressure, etc) of application. Coordination compounds, which present electron transfer between metal ion and an organic ligand associated with a change in electron multiplicity of the metal ion are named valence tautomers. The chemical equilibrium between two distinct electronic states in valence tautomers can be induced by the temperature and pressure change as well as by soft X-ray and light irradiation.Thermodynamic and structural data highlighting the mechanisms of valence tautomeric conversion can be found in the literature for materials build up with Cobalt and benzoquinones such as the 3,5-di-tert-buthyl-semiquinonate. However, to the best of our knowledge, there is no example of compounds showing valence tautomerism build up with cobalt and naphthoquinones. In the present work 2-hydroxy-1,4-naphthoquinone and 1,2-naphthoquinone were used as redox active ligands in the search for new valence tautomeric compounds with cobalt. Three new coordination compounds of cobalt and lawsone (lau), [Co(lau)2(im)2], [Co(lau)2(phen)], [Co(lau)2(bpy)] where im=1H-Imidazole, phen=1,10- phenanthroline and bpy =2,2-bipyridine were synthesized. The new compounds were characterized by infrared (IR),UV-vis spectroscopy, electron paramagnetic resonance (EPR) and cyclic voltammetry. The three dimensional structures were determined using single crystal X ray diffraction techniques. However, within the investigated temperature range neither X ray diffraction nor EPR data showed the presence of valence tautomerism in the materials, mainly due to the electrochemical properties of the lawsonate. Nevertheless the structural features of the compounds as well as their supramolecular packing motifs suggest that naphthoquinones can be an alternative for the synthesis of compounds showing valence tautomerism. Five new compounds with the general formula [Co(naft)2NN] where naft stands for 1,2- naphthoquinone and NN represents amine ancillary ligands, bpy, dpa, 4-CN-py, tmeda and dmap were synthesized and characterized. The IR spectra of the materials showed that the use of [Co2(CO)8] allows the reduction of 1,2-naphthoquinone to a radicalar species. The EPR data in the 298 K to 77 K range revealed the presence of eight hyperfine lines with a center in g = 2 which is characteristic of systems with Co3+ and radicalar species. The UV-vis spectra at room temperature showed the predominance of Co2+ in relation to Co3+. Ab initio calculations demonstrated the electronic similarity of cobalt-1,2-napthoquinone compounds with known cobalt-benzoquinone compounds, as they kept the same electronic and structural characteristics, indicating the possibility of existence of valence tautomerism in these new compounds.